Caregiver factors influencing nutritional status of preschool children in Mwingi West, Kitui County Kenya. - Mbijiwe, Jane; Ndung’u, Zipporah; Kinyuru, John (My University, 2022)
Children are at an increased risk of malnutrition, with many undernourished children being highly susceptible to preventable premature death and morbidity. Insufficient dietary intake, infections, food insecurity, and inadequate care are the main causes of child malnutrition. These factors are sequentially influenced by caregivers’ characteristics. Despite this, the effect of a caregiver’s characteristics on a child's nutrition status has not been exhaustively studied in rural areas of Kenya. It is important to continuously examine the trends in the prevalence of malnutrition for effective interventions. Regular updates on the prevalence of malnutrition are crucial for appropriate interventions. In this study, the nutritional status of children was evaluated alongside their association with caregivers’ characteristics. The study was based in Migwani ward, Mwingi West Sub-County in Kitui County. The study was conducted between October and December 2020 and involved 106 caregivers with their 106 children aged 36–42 months. The characteristics of the caregivers were determined by the use of a pretested study questionnaire. To evaluate the nutritional status of children, the height and weight measures, age, and sex of the child were taken and transferred into the WHO Anthro software, and zscores were derived. The Statistical Package for the Social Sciences (SPSS) was used to carry out additional data analysis. Children's nutritional status and caregivers’ characteristics were bivariate tested to determine the association. In the present study, the prevalence of stunting was 33.0%, wasting was 15.1%, and underweight was 20.8%. In this study, the caregivers that had lower income had more children that were underweight (χ2 = 9.2 p = 0.02), stunted (χ2 = 10.4 p = 0.015) and wasted (χ2 = 16.9, p<0.001) compared to those with higher incomes. More so, the caregivers that were younger had more children that were wasted (χ2 = 20.04, p<0.001), stunted (χ2 = 9.65, p = 0.032) and underweight (χ2 = 8.26, p = 0.041). Households that were headed by women had more children that were stunted (p = 0.022), wasted (p = 0.041) and underweight (p = 0.003). Similarly, respondents with lower education levels had more children that were stunted (χ2 = 14.02, p = 0.003), wasted (χ2 = 4.85, p = 0.037) and underweight (χ2 = 4.76, p = 0.045). In this study, the caregiver’s occupation was significantly associated with children's stunting (χ2 = 12.23, p = 0.007) and underweight levels (χ2 = 6.12, p = 0.034). The caregiver’s occupation had no influence on the children's wasting levels. The present study found that the marital status of a caregiver did not influence a child's nutritional status. These study results affirm that nutritional problems of stunting, wasting, and underweight among preschool children in Kitui County require public health actions. That caregivers’ characteristics play a role in the nutritional status of preschool children in Kitui County. Based on these study findings, priority should be given to children's nutrition programs that incorporate the dynamics of caregivers' characteristics. By doing this, such programs will be more effective.
Keywords: Nutritional Status; Caregivers Factors; Children; Rural Areas